LA HISTORIA CULTURAL EN GUATEMALA: UN ITINERARIO POR RECORRER. REFLEXIONES HISTORIOGRÁFICAS. - Cal Montoya, José Edgardo (2006)
This article sets forth a balance of the Guatemalan cultural history in the framework of a wide scope of historiographic fields, such as daily living, art, science, literature and others that relate to the subject area of cultural phenomena. Furthermore, it addresses the way in which the renewal of historical research in Europe was warmly welcomed in the development of historical science in the Central American region. This work explores the making of cultural history in Guatemala through publications disseminated by widely experienced schools and historical research centers, with the purpose of defining the most developed subjects, the problems expounded, and the theoretical-methodological concerns of the Guatemalan historians.